Konsistensi Regulasi Pengupahan Di Indonesia Terhadap Keputusan Menteri Ketenagakerjaan Republik Indonesia Nomor 76 Tahun 2024 Tentang Pedoman Pelaksanaan Hubungan Industrial Pancasila (HIP) Pada Sektor Pengupahan Di Tengah Globalisasi Pekerjaan - Alan Joan Saputra; Ayunita Nur Rohanawati (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research was motivated by the passing of the latest regulations issued by the Ministry of Manpower in the form of Ministry of Manpower Decree Number 76 of 2024 concerning Guidelines for Implementing Pancasila Industrial Relations (HIP) amidst the globalization of work in Indonesia. Considering the various existing labor regulations, many of them have not been able to resolve wage problems in Indonesia. This can be seen from the gap between das sollen and das sein in legal wage standards. The question is whether this harmony or gap shows that the stripping system in Indonesia is in line with the values of Pancasila or not. So what can be done with the ratification of Minister of Manpower Decree Number 76 of 2024 concerning Guidelines for the Implementation of Pancasila Industrial Relations (HIP) so that it can answer problems related to workers’ wages and whether the wage system in Indonesia is in accordance with the Pancasila philosophy. Thus, the formulation of the problem in this research is: First, how consistent is the wage regulation in Indonesia with the Indonesian Minister of Manpower’s Decree Number 76 of 2024 concerning Guidelines for the Implementation of Pancasila Industrial Relations (HIP) in the wage sector amidst the globalization of work. Second, whether wage policy in Indonesia is in accordance with the basic industrial relations philosophy of Pancasila. This research was carried out using a normative juridical research method which was aimed only at written legislation or other related legal materials. The results of the research conducted by researchers are that the role and cooperation between the parties involved in Pancasila industrial relations is still felt to be lacking and wage policies in Indonesia are in accordance with the basic philosophy of Pancasila industrial relations but reform is needed considering the very rapid changes in the wage sector in employment.